2022
DOI: 10.47391/jpma.4167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transformational leadership intervention of head nurses among front-line solders (staff nurses) working in government hospital

Abstract: Objective: To assess the impact of transformational leadership intervention among head nurses on staff nurses in improving job performance. Method: The quasi-experimental study was conducted from December 2020 to August 2021 at the public-sector Services Hospital, Lahore, Pakistan, and comprised head nurses and staff nurses enrolled through multistage cluster random sampling technique. Sixteen weeks of transformational leadership interventions were organised in morning and evening shifts. Pre- and post-interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is believed that respect and courtesy shown by the leaders toward the staff (and vice versa) as a leadership value and a corporate culture ensures a safe and comfortable work milieu where the staff from different countries can feel secure and inspired to deliver the services expected from them. The respect that they have for themselves drives nursing leaders to excel in the outstanding field of nursing [19]. Moreover, this demonstrates the presence of effective communication among intercultural teams and the provision of high-quality, secure patient care [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that respect and courtesy shown by the leaders toward the staff (and vice versa) as a leadership value and a corporate culture ensures a safe and comfortable work milieu where the staff from different countries can feel secure and inspired to deliver the services expected from them. The respect that they have for themselves drives nursing leaders to excel in the outstanding field of nursing [19]. Moreover, this demonstrates the presence of effective communication among intercultural teams and the provision of high-quality, secure patient care [20].…”
Section: Discussionmentioning
confidence: 99%
“…Australian researchers (Leggat et al 2016) conducted one of the eight studies, while their American counterparts did the others (Abraham 2011; Chappell and Richards 2015; Fitzpatrick et al 2016;Hamed, Eid, and Hasanin 2023;MacPhee et al 2014;Mushtaq, Hussain, andParveen 2022, Shen et al 2018;Xie, Ding, and Zhang 2021).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In eight studies, cognitive abilities were identified as a fundamental component of the programmes designed to foster nurses' clinical leadership (Abraham 2011;Fitzpatrick et al 2016;Hamed et al 2023;Leggat et al 2016;MacPhee et al 2014;Mushtaq et al 2022;Shen et al 2018;Xie et al 2021).…”
Section: Interventions To Promote Leadershipmentioning
confidence: 99%
See 2 more Smart Citations